Customer expectation towards fresh milk and juice home delivery service / Nurul Nadia Abd Malek - Abd Malek, Nurul Nadia (2010)
Magnolia embarks on fresh milk home delivery just in time for the perfect breakfast. “Magnolia Fresh Milk Home Delivery” service which brings the creamy, yummy goodness of Magnolia Milk right to your doorstep. Taking a cue from the milkmen of yesteryear, the newly launched Magnolia Fresh Milk Home Delivery service from F&N Dairies (M) Sdn Bhd is the first of its kind in Malaysia. Van added industry findings indicated that milk consumption amongst Malaysians is still relatively low and this service is one way to encourage Malaysians to drink milk, especially fresh milk on a regular basis as it is a rich source of protein and calcium for all walks of life. In recent years, home deliveries have been making a comeback especially to cater to the needs of typical families. Kicking off in April, the Magnolia delivery service is timely as nowadays, families are increasingly busy tending to their daily routines. It offers consumers the convenience of delivery while helping them get their dose of Magnolia fresh milk without the hassle.